2011
DOI: 10.1002/met.294
|View full text |Cite
|
Sign up to set email alerts
|

Reducing errors of wind speed forecasts by an optimal combination of post‐processing methods

Abstract: Seven adaptive approaches to post-processing wind speed forecasts are discussed and compared. Forecasts of the wind speed over 48 h are run at horizontal resolutions of 7 and 3 km for a domain centred over Ireland. Forecast wind speeds over a 2 year period are compared to observed wind speeds at seven synoptic stations around Ireland and skill scores calculated. Two automatic methods for combining forecast streams are applied. The forecasts produced by the combined methods give bias and root mean squared error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 22 publications
0
47
0
Order By: Relevance
“…Wind speeds can show large spatial variability below typical NWP model grid cell sizes [e.g., Winstral et al , ]. Without using terrain parameters but also covering hilly areas Sweeney et al [] found reduced wind speed errors when applying adaptive statistical postprocessing methods on NWP output. This approach required training each day on data from previous days and was also only tested for stations around Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…Wind speeds can show large spatial variability below typical NWP model grid cell sizes [e.g., Winstral et al , ]. Without using terrain parameters but also covering hilly areas Sweeney et al [] found reduced wind speed errors when applying adaptive statistical postprocessing methods on NWP output. This approach required training each day on data from previous days and was also only tested for stations around Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the binning approach employed in Sweeney et al (), forecasted wind direction is here implemented in Eq. as Fourier expansion terms alignleftalign-1f(wd)=k=1Nakcos(kwd)+bksin(kwd),wd(π,π],align-2 up to fifth order ( N = 5), to approximate wind speed dependence on a periodic function of forecasted wind direction w d .…”
Section: Methodsmentioning
confidence: 99%
“…Wilks (2002) describes how the wind speed data could be transformed to a normal distribution by taking the square root of the distribution. Thorarinsdottir and Gneiting (2010) developed the EMOS approach for wind speed using a truncated normal distribution with a cut-off at zero to represent the data.…”
Section: Previous Studiesmentioning
confidence: 99%